2005
DOI: 10.2193/0022-541x(2005)069[1181:sviwns]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Waterfowl Nesting Success and Its Relation to Cover Management in the Canadian Prairies

Abstract: Early hatched waterfowl are more likely to enter the breeding population. Managers' primary tool to increase nesting success in the Prairie Pothole Region (PPR) of North America is managing upland vegetation for duck nesting cover. To determine whether managed covertypes affect early‐season nesting success, we modeled seasonal variation in nesting success using >17,000 duck nests found in managed and unmanaged covertypes in prairie Canada from 1993 to 2000. Nesting success was higher in most managed covertypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 19 publications
4
59
1
Order By: Relevance
“…Nest survival of ducks in spring-seeded cropland is low compared to most other habitat types (Klett et al 1988, Greenwood et al 1995), ranging from < 1-4% (Richkus 2002), 2% (Greenwood et al 1995), and 7% (Klett et al 1988). Devries et al (2008a) reported a relatively high nest success rate of 12% in spring-seeded cropland and opined that this may have been a result of their inclusion of late-season nests because success rates in spring-seeded cropland can increase substantially throughout the growing season (Emery et al 2005). Recently, one of us (JHD) modeled mean pintail nest success in spring-seeded cropland to be 5.1% (i.e., daily survival rate = 0.9111 + 0.0146; Table 2) based on the fate of 153 nests in cropland (Devries et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Nest survival of ducks in spring-seeded cropland is low compared to most other habitat types (Klett et al 1988, Greenwood et al 1995), ranging from < 1-4% (Richkus 2002), 2% (Greenwood et al 1995), and 7% (Klett et al 1988). Devries et al (2008a) reported a relatively high nest success rate of 12% in spring-seeded cropland and opined that this may have been a result of their inclusion of late-season nests because success rates in spring-seeded cropland can increase substantially throughout the growing season (Emery et al 2005). Recently, one of us (JHD) modeled mean pintail nest success in spring-seeded cropland to be 5.1% (i.e., daily survival rate = 0.9111 + 0.0146; Table 2) based on the fate of 153 nests in cropland (Devries et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Survival can vary with age of the nest and nest initiation date in both grassland passerines and uplandnesting ducks, although time-specific patterns in survival rates are reportedly inconsistent among regions and species (emery et al 2005;Grant et al 2005;Davis et al 2006;Grant and Shaffer 2012). Survival was highest for nests initiated early in the breeding season for five of the seven species in our study.…”
Section: Nest Survivalmentioning
confidence: 56%
“…for many bird species, nest survival can vary with age of the nest, date in the nesting season, or year. recent studies conducted in the northern Great Plains show that duck and passerine nest survival is influenced by the date a nest is initiated (emery et al 2005;Grant et al 2005;Davis et al 2006;Kerns et al 2010;Grant and Shaffer 2012). More specifically, Grant et al (2005) demonstrated that Claycolored Sparrow (Spizella pallida) and Vesper Sparrow (Pooecetes gramineus) nests initiated early in the season had higher survival rates than nests initiated later in the season.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have reported seasonal variation in nest success in ducks (Klett and Johnson 1982, Hepp and Kennamer 1993, Emery et al 2005, Devries et al 2008, which may be related to age or condition of the nesting hen (Hohman 1986) or changes in predator behavior or nesting cover throughout the season. Such changes might also be influenced by nest and nest-site characteristics that influence predator encounter rates (Gerell 1970, Barding andNelson 2008).…”
Section: Discussionmentioning
confidence: 99%